Dietary interventions in obesity: a narrative review - Dudašova Petrovičova, Olina; Djuričić, Ivana; Ivanović, Nevena; Dabetić, Nevena; Dodevska, Margarita; Ilić, Tijana (Archives of Pharmacy, 2024)
The World Health Organization highlights that in 2022 around 890 million adults and 160 million children and adolescents globally were obese, indicating a significant public health concern. Obesity results from an energy imbalance, where calorie intake exceeds calorie expenditure, leading to an increase in the size of fat cells and subsequently to metabolic dysfunction and inflammation. Management of obesity involves lifestyle adjustments, including dietary modifications and increased physical activity, with calorie-restricted diets and meal replacements often recommended to achieve weight loss and lower overall energy intake. Weight loss programs include a low-carbohydrate, low-fat, or high-protein diet. In addition, the influence of the Mediterranean diet and dietary fiber on regulating body weight has been increasingly studied in recent years. Dietary products for weight control, including meal replacements, are regulated and offer options for people who want to lose weight. More personalized nutrition approaches are emerging that focus on individual needs, genetic factors and gut microbiota composition to optimize health outcomes. Although personalized nutrition promises to explain how nutrition-related health problems may be solved, further research should investigate health outcomes in individuals living with obesity.